PENYULUHAN KARIES GIGI DENGAN MEDIA SLIDE PADA SISWA KELAS VII SMP NEGERI 3 SAMARINDA TAHUN 2020 - Wulandari, Kartina (Universitas Muhammadiyah Tapanuli Selatan, 2021)
According to Riskesdas (2017), the East Kalimantan Province has an active caries prevalence of 49.6% in 2016 and increased to 63.3% in 2017, but the DMF-T index value decreased from 5.08 to 4.7. These data indicate that the prevalence of active caries and the DMF-T index value in East Kalimantan are still higher than the national average. Based on the results of observations made on Grade VII students of SMP Negeri 3 Samarinda, they had never been given counseling on dental caries, even though there were students who had dental caries. The purpose of this service is to provide information about health education and information about the factors that cause dental caries and also the consequences of this caries. This activity is carried out by the public health faculty using several tools such as laptops, LCDs, projectors, stationery and flayer. The method used was counseling then continued with a Focus Group Discussion (FGD).